Effectiveness of Bilateral Uterine Artery Ligation in Prevention of Primary PPH in Type 4 Placenta Previa - Naz, Tahira; Sadaf, Rabeea; Qayum, Sana; Fatima, Laraib (Indus Journal of Bioscience Research, 2025)
Background: Primary postpartum haemorrhage (PPH) is a major contributor to the morbidity and mortality of mothers, especially in individuals with type four placenta previa. Effective interventions to prevent PPH during cesarean sections are essential. Bilateral uterine artery ligation is a potential technique for reducing the incidence of PPH and associated complications. Objective: To evaluate the effectiveness of bilateral uterine artery ligation compared to conventional cesarean section in preventing primary PPH in patients with type 4 placenta previa. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from July 2024 to January 2025 in the Department of Obstetrics and Gynaecology at LRH Peshawar. Methodology: A total of 336 patients aged 20–40 years with type 4 placenta previa and gestational age >32 weeks were randomized into two groups. Group A (n=168) underwent bilateral uterine artery ligation during cesarean section, while Group B (n=168) underwent conventional cesarean section. The primary outcome was the incidence of PPH within 24 hours of delivery, defined as blood loss >1000 mL. Results: Group A demonstrated significantly higher efficacy (73.8%) in preventing PPH compared to Group B (44%) (p=0.000). Stratified analysis revealed consistently higher efficacy in Group A across all age groups, gestational ages, parity levels, and socioeconomic categories. Conclusion: Bilateral uterine artery ligation is an effective and safe procedure for preventing primary PPH in patients with type 4 placenta previa.